2006
DOI: 10.1111/j.1939-1676.2006.tb01812.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Aspects and Clinical Outcomes of Canine Renal Hemangiosarcoma

Abstract: Background: Hemangiosarcoma (HSA) is a common solid tumor of the spleen, heart, and skin of dogs. Renal HSA represents an uncommon anatomic variant, with little reported about its biologic behavior and clinical outcome. Hypothesis: That renal HSA is associated with longer survival than other visceral forms of HSA. Animals: 14 dogs with renal HSA. Methods: Medical records from 1999 to 2004 were searched for dogs with histopathologically confirmed renal HSA, and data relevant to clinical signs, treatments, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…[9][10][11][12][13][14] Other treatments, including administration of α-aminocaproic acid and formalin (IV) have not been reported in camelids. Medical management of hematuria should involve supportive care, including administration of blood transfusions and antimicrobials for bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14] Other treatments, including administration of α-aminocaproic acid and formalin (IV) have not been reported in camelids. Medical management of hematuria should involve supportive care, including administration of blood transfusions and antimicrobials for bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Medical management of hematuria should involve supportive care, including administration of blood transfusions and antimicrobials for bacterial infections. In most reports, 10,12,14,15 nephrectomy is thought to be required to completely resolve blood loss. [9][10][11][12][13][14] Other treatments, including administration of α-aminocaproic acid and formalin (IV) have not been reported in camelids.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound imaging is often used in the evaluation of dogs with suspect hemoperitoneum for both diagnosis and for identifying sources of bleeding before surgery. Splenic masses are the most commonly reported source of hemorrhage in dogs with tumors; however, other abdominal organs may be involved, including the liver, adrenal glands, and kidneys . Previous reports have shown that dogs with splenic masses and concurrent hemoperitoneum have high rates of malignancy .…”
Section: Introductionmentioning
confidence: 99%
“…In cats, only single cases of hemangiosarcoma have been described to date (4). While hemangiosarcoma represents a frequent primary tumor of the spleen and skin, it has also been diagnosed in kidneys (5). The tumor occurs most frequently in older (more than 10 years old) dogs.…”
Section: Introductionmentioning
confidence: 99%